Tantamount: A Comparative Study in Analyzing the Effectiveness of Covid-19 Response Policy in Indonesia and Thailand - Januari Pratama Nurratri Trisnaningtyas; Alif Rizky Maulana; Alif Valentino Briliyan; Damar Dwi Syahrial; Sami (WIMAYA, 2022)
Over the past few years, the world has experienced a pandemic with the spread of the COVID-19 outbreak. Every country attempt to minimize virus transmission through the implementation of various policies such as implementing travel restrictions, the closure of International borders, mass vaccination, and stabilizing the economy and welfare. This research aims to compare the effectiveness of the domestic policies in Indonesia and Thailand in responding to the COVID-19 pandemic and analyze the impact that followed the implementation of the policies. The authors use comparative theory by analyzing two main indicators: the health and economic sectors. The results show that the policies implemented by the Thai government are more effective in reducing the rate of transmission of COVID-19 and recovering the economic sector during a pandemic. The authors argue that the effectiveness of the Thai government's policies is a major factor in the country's post-pandemic recovery.